2021
DOI: 10.1108/prt-02-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of congo red dye from aqueous solutions using Mo-doped CoFe2O4magnetic nanoparticles

Abstract: Purpose The main purpose of this paper is to investigate the adsorption properties of CoFe1.9Mo0.1O4 magnetic nanoparticles (CFMo MNPs) using, anionic dye “congo red (CR)” as a model of water pollutants. Design/methodology/approach The magnetic nano-adsorbent was synthesized via sol-gel process. Different techniques including; Fourier transform infrared spectroscopy, point of zero charge, scanning electron microscope and X-ray powder diffraction were used to characterize the prepared adsorbent. Adsorption ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…However, when the temperature was increased beyond 328 K, the adsorption efficiency was reduced. These results corroborate those reported by Amar et al who utilized Mg-doped CoFe 2 O 4 nanoparticles to remove CR dye from aqueous solutions [9].…”
Section: Effect Of Initial Cr Dye Concentration the Results Insupporting
confidence: 92%
See 2 more Smart Citations
“…However, when the temperature was increased beyond 328 K, the adsorption efficiency was reduced. These results corroborate those reported by Amar et al who utilized Mg-doped CoFe 2 O 4 nanoparticles to remove CR dye from aqueous solutions [9].…”
Section: Effect Of Initial Cr Dye Concentration the Results Insupporting
confidence: 92%
“…Furthermore, the intraparticle diffusion model was employed to better understand the underlying adsorption mechanism and the rate-determining step. From Equation (9), the intraparticle diffusion model suggests that if by plotting q t versus t 0:5 yields a linear graph passing through the origin, then intraparticle diffusion is the only rate-limiting step of the adsorption process. Figure 13(c) shows that the plot of q t versus t 0:5 is not linear over the whole range of time and did not pass through the origin.…”
Section: Biosorption Kineticmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that the proposed adsorption process may be described by the pseudo-second-order q e q e model. Given that the experimental adsorption data ts the pseudo-second-order model well, it can be concluded that the characteristics of the adsorbent and adsorbate materials in uence the adsorption mechanism [39]. The pseudo-second-order model is based on the hypothesis that rate-determining step may be chemical sorption or chemisorption involving electron sharing or exchange between prepared adsorbents and two proposed adsorbates, i.e.…”
Section: Adsorption Kineticsmentioning
confidence: 96%
“…Separate 1 ml from the suspension adsorbent solution after every 10 minutes and centrifuge for 5 minutes, measure the absorbance using UV spectrophotometer at wavelength 496 nm for CR and 664nm for MB. Used the following equation to estimate the removal percentage (%) [19,24].…”
Section: Adsorption Experimentsmentioning
confidence: 99%